ANALISA PERANCANGAN SISTEM PAKAR DIAGNOSIS PENYAKIT PADA AYAM MENGGUNAKAN METODE CERTAINTY FACTOR BERBASIS WEBSITE - Muhamad Dodi Alfayet; Jazuli Mukhtar (CV. Multi Kreasi Media, 2022)
Individual farms and small farmers, including the majority of farmers who fail to raise livestock due to lack of information in dealing with diseases and also a lack of doctors in small areas, lack of information about diseases in chickens and the inability of farmers to diagnose diseases in chickens early will result in delays in treatment and lead to death. on chicken. Farmers who have smaller herds will suffer as a result of this. Other chickens can also get the disease that is spread by previously infected chickens. Therefore, we need a system that can provide advice on chicken diseases, and the solution is to create an expert system application to diagnose chicken diseases using a web-based system. In this study, the author uses the certainty factor method with UML (Unified Modeling Language) as development tools. Researchers will use the Certainty factor method with expert knowledge to match the symptoms into a disease that can make it easier for farmers to diagnose diseases in their chickens. Making this application using the programming language PHP and MYSQL for database processing. This study resulted in a diagnostic system in chickens to facilitate farmers in diagnosing chicken diseases.